Avalanche Danger on the Highways of the Samegrelo-Zemo Svaneti Region (Georgia) - Pipia, Mikheil; Gorgijanidze, Sophio; Beglarashvili, Nazibrola; Kobakhidze, Natela; Jintcharadze, Gocha (European Journal of Sustainable Development, 2023)
The importance of highways in the mountainous regions of Georgia is very great for the socio-economic development of the country. Such natural disasters as snow avalanches significantly damage the road infrastructure, create delays in movement, often cause human casualties. Therefore, in order to implement preventive measures, the study of avalanche hazards on highways is of great importance. Mestia municipality of Samegrelo-Zemo Svaneti region (Zemo Svaneti) is characterized by mountainous and high-mountain terrain, snow avalanches are frequent, including on sections of highways. Avalanche hazards on highways of Mestia municipality of Samegrelo-Zemo Svaneti region and climatic factors of their occurrence are studied. The data of the Mestia meteorological station on air temperature and solid precipitation covering the years 1961-2021 have been processed. A geo-informational map of the avalanche danger of highways in the Samegrelo-Zemo Svaneti region has been compiled. Keywords: Snow avalanches, climate, natural disaster, highways, geoinformation map